Fractal of Periodic Spacetime Sequences as a framework for an interoperable metaverse - Łukawski, Adam (Paris Europia Productions, 2023)
This paper proposes a new conceptual framework for the creation of an interoperable metaverse seamlessly incorporating AI and blockchain technologies. To achieve this, current issues of interoperability within the discipline’s state-of-the-art are first identified. Next, a new virtual ontology of the interoperable metaverse is proposed, inspired by recent developments in assemblage theory and in specific concepts by Gilles Deleuze, Manuel DeLanda, and Paulo de Assis. In the third and fourth parts of this paper, a new technical solution is presented: a taxonomy of Periodic Spacetime Sequences, devised for practical implementation of a new distributed version control system. This solution could offer an innovative framework for the interoperable metaverse, which could be built using the proposed taxonomy.
FRIS
Editorial review
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music